The Historical writings - Coomber, Matthew J. M.; Page, Hugh R., Jr; Yee, Gale A., 1949- (Fortress commentary on the Bible., 2016)
This concise commentary on the Historical Writings, excerpted from the Fortress Commentary on the Bible: The Old Testament and Apocrypha, engages readers in the work of biblical interpretation. Contributors from a rich diversity of perspectives connect historical-critical analysis with sensitivity to current theological, cultural, and interpretive issues. Introductory articles describe the challenges of reading the Old Testament in ancient and contemporary contexts, relating the biblical theme of "the people of God" to our complex, multicultural world, and reading the Old Testament as Christian Scripture, followed by a survey of "Themes and Perspectives in the Historical Writings." Each chapter (Joshua through Esther) includes an introduction and commentary on the text through the lenses of three critical questions: The Text in Its Ancient Context. What did the text probably mean in its original historical and cultural context? The Text in the Interpretive Tradition. How have centuries of reading and interpreting shaped our understanding of the text? The Text in Contemporary Discussion. What are the unique challenges and interpretive questions that arise for readers and hearers of the text today? The Historical Writings introduces fresh perspectives and draws students, as well as preachers and interested readers, into the challenging work of interpretation